A Study on the Comprehensive and Integrated Workplace Safety and Health Services in Singapore. Issue 9 (September 2015) - Chia, Sin Eng; Wah, Lim John; Khim, Judy Sng Gek; Yoong, Joanne; Lim, Raymond Boon Tar; Seng, Chia Kee
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to evaluate the level of comprehensiveness and integration of workplace safety and health (WSH) services (safety, occupational health, and well-being) in Singapore. Methods: Thirty workplaces from five different sectors comprising more than 28, 000 workers were assessed using three custom-developed tools. Results: One quarter of the workplaces have applied the principles of comprehensive and integrated WSH. Among those that managed WSH comprehensively, workers were 4.4 times (95% confidence interval [CI], 2.33 to 8.25) more likely to be proud to work for their company, 7.4 times (95% CI, 3.96 to 13.90) more likely to be satisfied with their current job, and 1.7 times (95% CI, 1.21 to 2.32) more likely to balance the demands of work and home. Conclusions: There is a need to enhance awareness and education on comprehensive and integrated WSH in Singapore companies.